Synthesis, Cytotoxicity and Anti-Proliferative Activity against AGS Cells of New 3(2H)-Pyridazinone Derivatives Endowed with a Piperazinyl Linker - Mehmet Abdullah Alagöz; Zeynep Özdemir; Mehtap Uysal; Simone Carradori; Marialucia Gallorini; Alessia Ricci; Susi Zara; Bijo Mathew (MDPI AG, 2021)
Novel twenty-three 3(2H)-pyridazinone derivatives were designed and synthesized based on the chemical requirements related to the anti-proliferative effects previously demonstrated within this scaffold. The introduction of a piperazinyl linker between the pyridazinone nucleus and the additional (un)substituted phenyl group led to some compounds endowed with a limited cytotoxicity against human gingival fibroblasts (HGFs) and good anti-proliferative effects against gastric adenocarcinoma cells (AGS) as evaluated by MTT and LDH assays, using doxorubicin as a positive control. Successive analyses revealed that the two most promising representative compounds (12 and 22) could exert their effects by inducing oxidative stress as demonstrated by the hydrogen peroxide release and the morphological changes (cell blebbing) revealed by light microscopy analysis after the haematoxylin-eosin staining. Moreover, to further assess the apoptotic process induced by compounds 12 and 22, Bax expression was measured by flow cytometry. These findings enlarged our knowledge of the structural requirements in this scaffold to display valuable biological effects against cancerous cell lines.